Usos e práticas net-ativistas de consumidores nas redes digitais - Freire, Gustavo David Araújo (2015)
In the context of the new economy, fostered mainly by information and communication technologies and economic liberalization and deregulation, the relations between organizations and consumers are changed. Consumption is regarded as something "eminently social, correlative and active", contributing to the practice of citizenship and ratifying an "Age of Rights'. The disregard and disrespect faced by consumers in the relationship marketing have led them to adopt a behavior based on affirmative practices, in environments such as social networking sites. In this sense, this study aims at analyzing the net-activist practices of consumers of companies Tim, Oi, Claro and Vivo - that offer fixed-line, mobile and internet services - in their respective Facebook pages, understood as a legitimate customer service, in the social context of mediatization. With quantitative and qualitative nature and under an exploratory approach, the analysis of the object is constituted as a case study of comparative type, based on the intensive indirect observation by the bias of non-participant observation. The investigation identified, initially, that phone companies are the ones that receive more complaints which consumers turn to their institutional pages as an alternative way to achieve their claim. This way, the companies consolidate one legitimating space of customer service. However, social networking platforms used as SAC 2.0 are not regulated by the State and, therefore, the promptness of the customer service is drifting by the phone companies.